Pekan Penerimaan Anggota Baru GMNI Dalam Membentuk Anggota Marhaenis Yang Progresif Menuju Indonesia Emas 2045 - Ade Putra Ode Amane; Sri Ayu Laali; Freshdy Nia; Maria Ulfa; Rifat Hakim; Anggi Afriawan; Rika Afriliani Alapia (Universitas Muhammadiyah Manado, 2022)
The research method in data collection uses primary data and secondary data and the technical model of data analysis uses an inductive model. The Week of Admission of New Members (PPAB) for the GMNI Luwuk-Banggai Branch Leadership Council will be held on 24-26 September 2022 at the General Assembly Hall (BPU) of Luwuk Village, Luwuk District, Banggai Regency with the theme